Just my type : a book about fonts - Garfield, Simon (Profile Books, 2011)
Just My Type is not just a font book, but a book of stories. About how Helvetica and Comic Sans took over the world. About why Barack Obama opted for Gotham, while Amy Winehouse found her soul in 30s Art Deco. About the great originators of type, from Baskerville to Zapf, or people like Neville Brody who threw out the rulebook, or Margaret Calvert, who invented the motorway signs that are used from Watford Gap to Abu Dhabi. About the pivotal moment when fonts left the world of Letraset and were loaded onto computers... and typefaces became something we realised we all have an opinion about. As the Sunday Times review put it, the book is'a kind of Eats, Shoots and Leaves for letters, revealing the extent to which fonts are not only shaped by but also define the world in which we live.'This edition is available with both black and silver covers.
Keywords: Type and type-founding : History; Type and type-founding : Psychological aspects; Typographers : Biography; Graphic design (Typography); Type and type-founding; Type and type-founding : Social aspects; graafinen suunnittelu; typografia; kirjaimet; kirjasinlajit; historia